Evaluation of the effect of 3-month bladder basic advice in children with monosymptomatic nocturnal enuresis. Issue 6 (December 2017) - Tkaczyk, Marcin; Maternik, Michał; Krakowska, Anna; Wosiak, Agnieszka; Miklaszewska, Monika; Zachwieja, Katarzyna; Runowski, Dariusz; Jander, Anna; Ratajczak, Dariusz; Korzeniecka-Kozyrska, Agata; Mader-Wołyńska, Izabella; Kiliś-Pstrusińska, Katarzyna
Summary: Introduction: Advice (BBA) into the standards of patients' care in both monosymptomatic and non-monosymptomatic nocturnal enuresis. Although the idea of this recommendation was clear and reflects clinical experience, duration and efficacy have not been definitely established. Recent data have demonstrated the lack of efficacy of BBA and a fierce discussion has ensued. The present study was aimed to assess the efficacy of BBA in a group of previously untreated children with primary monosymptomatic nocturnal enuresis (MNE). Study design: The study was a prospective interventional multicenter trial in a cohort of previously untreated MNE patients. Forty-nine children (36 males, 13 females, mean age 7.2 years) were included in the analysis. The treatment efficacy was assessed at the 30th, 60th, and 90th days of BBA. Results: We discovered that the mean number of wet nights decreased significantly ( p <  0.001) only after 3 months of BBA from 8.9 to 5.9 episodes every 2 weeks. BBA was fully successful in 2% o the children after 30 day, 12% after 60 days, and 18% after 90 days (Figure ). Partial response (by ICCS) was assessed for 8%, 20%, and 34% of the patients. We noted a relatively high rate of non-responders that decreased from 90% to 47% after 90 days. We detected no differences in BBA efficacy between children with night-time polyuria or decreased maximal voided volume. A lower number of wet nights initially predicted the response to the BBA. Discussion: Our study confirmed rather limited efficacy of BBA, similarly to previous observations, but provided more information on isolated MNE, because of a more specific study group and longer period of observation. The limitation of the study was lack of randomization. Conclusion: Our study revealed that in treatment-naïve children with monosymptomatic enuresis basic bladder training had a low (18%) and late effect, mostly pronounced after the third month of therapy. It seems that only if the patient presents with a favorable profile of bedwetting, occasionally and with a high maximum voided volume, it is worth maintaining BBA for a longer period of up to 3 months before initiating second-line therapy. In an unfavorable initial profile desmopressin or an alarm may be introduced much earlier. Figure Response to basic bladder advice in the study group.